Penentuan HPP Dengan Implementasi Job Order Costing Method Dalam Menentukan Harga Jual Produksi - Fadli, M. Rafli; Zanaria, Yulita; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the cost of production by implementing the Job Order Costing Method in determining the selling price of production (Study on K21 Clothing Convection Umkm Kotabumi Lampung Kota Bumi Lampung). This type of research is descriptive qualitative research. The instruments used in this research were interviews and observations. The data analysis techniques used are data reduction, data presentation and conclusions. The research results show that the calculation of the company's cost of production using the job order costing method has a difference. Calculation of the cost of production using the job order costing method is more accurate than company calculations because in this method the total production costs are grouped into three parts, namely raw material costs, labor costs and factory overhead costs to be charged to production costs to find the cost of goods sold. real production which also functions to determine the selling price of the product.